The Status of Resource Management and Certification in Tourism Sustainability Implementation Literature - Lampreia-Carvalho, Fatima (Journal of Tourism, Sustainability and Well-being, 2021)
The present article aims to explain why community-based natural resource management and tourism certification are the main concerns in academic literature on tourism sustainability implementation. The method of choice is a systematic review of literature based on the Prisma Statement for Systematic Reviews. Sources of interest were identified within the Web of Science Core Collection and other repositories. From a total of 430 records screened, 106 stable documents were selected and submitted to content analysis to create a matrix coding of mentions of sustainable tourism implementation in highly cited publications. A content analysis revealed that sustainable tourism implementation encompasses eight sub-categories of interest in current research outputs. Those sub-categories are: (1) Adaptive resource management (ARM), (2) Carbon mitigation approach; (3) Community-based Conservation Areas (CCAs) and Community-based ecotourism; (4) Community-based natural resource management (CBNRM); (5) Multiobjective Optimization model (6) Social reinvestment strategy; (7) Tourism Sustainability Certification and (8) Transition Management. The analysis revealed that implementation strategies such as Community-based natural resource management and the Tourism Certification Approach, covered 60 percent of all mentions of methods of sustainability implementation in the literature selected and should be treated as leading accelerators of tourism sustainability, yet much work needs to be done explain how and why a certain destination or tourism business meet set standards over time and across national contexts.